Cholinergic Grb2-Associated-Binding Protein 1 Regulates Cognitive Function. (7th June 2017) - Lu, Nan-Nan; Tan, Chao; Sun, Ning-He; Shao, Ling-Xiao; Liu, Xiu-Xiu; Gao, Yin-Ping; Tao, Rong-Rong; Jiang, Quan; Wang, Cheng-Kun; Huang, Ji-Yun; Zhao, Kui; Wang, Guang-Fa; et al.
Abstract: Grb2-associated-binding protein 1 (Gab1) is a docking/scaffolding molecule known to play an important role in cell growth and survival. Here, we report that Gab1 is decreased in cholinergic neurons in Alzheimer's disease (AD) patients and in a mouse model of AD. In mice, selective ablation of Gab1 in cholinergic neurons in the medial septum impaired learning and memory and hippocampal long-term potentiation. Gab1 ablation also inhibited SK channels, leading to an increase in firing in septal cholinergic neurons. Gab1 overexpression, on the other hand, improved cognitive function and restored hippocampal CaMKII autorphosphorylation in AD mice. These results suggest that Gab1 plays an important role in the pathophysiology of AD and may represent a novel therapeutic target for diseases involving cholinergic dysfunction.